"Fruits of Unrulie Multitudes": Liberty, Popularity, and Meanings of Violence in the English Atlantic, 1623–1625. (April 2020) - Beaver, Daniel C.
Abstract: Using neglected evidence of organized, state-like, internecine violence among English settlers in New England during the 1620s and 1630s, this essay engages with recent archipelagic approaches to the early modern English public sphere and with studies of the English state and political culture in order to argue for the existence of an important, semipublic Atlantic political discourse during the decades preceding the civil wars in the British Isles. It focuses on the distinctive political dynamics of Atlantic fishing stages during the early seventeenth century and on the violent confrontation between the Dorchester and Plymouth companies in 1625 over the control of the Cape Ann stage on Massachusetts Bay. The rumors, news, and formal reports that flowed from such incidents show how diffuse English ideologies assumed the form of opposed groups, armed and mobilized in the manner of free states, and confirmed fears of such violent episodes as threats to orderly governance in a political society conceived in Atlantic imperial terms. By examining the communication of and responses to this perceived threat during the late 1620s and 1630s, the essay reveals how an Atlantic discourse of "liberty, " "orderly commonweal, " and "popularity" influenced English political culture and policy and the institutions of Atlantic governance before the English Civil War.